1983
DOI: 10.1038/icb.1983.50
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐mediated Immune Response to Ross River Virus in Mice: Evidence for a Defective Effector Cell Response

Abstract: Summary Spleen cells recovered from mice during a primary infection with Ross River virus showed a virus‐specific proliferative response when challenged in vitro. The majority of the proliferating cells were T‐lymphocytes. In contrast, there was liltle detectable migration inhibition factor produclion by these spleen cells and little or no virus‐specific cytotoxic activity. Sub‐cutaneous challenge with virus elicited a weak delayed type hypersensitivity reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Additionally, an early report on RRV infection in mice showed virus-specific T cell proliferation when exposed to virus ex vivo (77), and a recent report on CHIKV infection in mice demonstrated that spleen and footpad-infiltrating T cells could produce IFN-γ after ex vivo stimulation with virus (32). Additionally, several studies have shown virus-specific T cell responses following immunization with different CHIKV vaccines in mouse and macaque models (36, 78), indicating an expansion and activation of virus-specific T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an early report on RRV infection in mice showed virus-specific T cell proliferation when exposed to virus ex vivo (77), and a recent report on CHIKV infection in mice demonstrated that spleen and footpad-infiltrating T cells could produce IFN-γ after ex vivo stimulation with virus (32). Additionally, several studies have shown virus-specific T cell responses following immunization with different CHIKV vaccines in mouse and macaque models (36, 78), indicating an expansion and activation of virus-specific T cells.…”
Section: Discussionmentioning
confidence: 99%
“…We found that Sindbis virus-primed NW-enriched T cells from C3H mice responded well to homologous but not to VEE virus stimulation (unpublished observation). Aaskov et al (1983) observed a virus-specific lymphoproliferative response with the alphaviruses Ross River, Getah and Sindbis, all antigenically unrelated. When we used a battery of antigenically related VEE subtype viruses to stimulate VEE TC-83 virus-primed T cells, the magnitude of the lymphoblastogenic response correlated with the antigenic classification scheme proposed by Young & Johnson (1969) based on kinetic HI using spiny rat antisera.…”
Section: Discussionmentioning
confidence: 97%
“…A virus-specific proliferative response was noted in a limited study with Getah, Ross River and Sindbis viruses (Aaskov et al, 1983).…”
Section: Introductionmentioning
confidence: 99%